Breastfeeding and Depression - Abdillah Husada (Open Access Indonesian Journal of Medical Reviews, 2021)
Pregnancy and postpartum depression frequently occurances, and that depressed women at pregnancy are usually depressed at the postpartum period. A literature review was conducted in the electronic databases PubMed and Google Scholar using the index terms “breast feeding” and “pregnancy depression” and “postpartum depression”, and “hormones”. Two investigators independently evaluated the titles and abstracts in a ﬁrst stage and the full text in a second stage review. All types of studies were included for this study, such as randomized controlled trials, systematic reviews, literature reviews, and pilot studies published between 2010 and 2021. This search resulted in 12 papers. The literature consistently shows that breastfeeding provides a wide range of beneﬁts for both the child and the mother. The psychological beneﬁts for the mother are still in need of further research. Breastfeeding can promote hormonal processes that protect mothers against postpartum depression by attenuating cortisol response to stress. However, the mother whom giving birth then directly breastfeeding their child, will reduce the mothers stress.